Nanoparticles for immune system targeting. Issue 9 (September 2017) - Du, Juan; Zhang, Yu Shrike; Hobson, Divia; Hydbring, Per
Highlights: Vast potentials of combining nanoparticles with immune therapy. Nanoparticles as adjuvants or carriers for vaccination and targeted therapies. Disease therapies using nanoparticles triggering innate immunity. Disease therapies using nanoparticles triggering adaptive immunity. Abstract : Nanoparticles (NPs) are found in numerous applications used to modulate the immune system. They serve as drug delivery carriers or vaccine adjuvants and are utilized as therapeutics against a variety of diseases. NPs can be engineered to target distinct cellular components representing multiple pathways of immunity. The combination of NPs with immune system-targeting moieties has paved the way for improved targeted immune therapies. Here we provide an update of recent progress in this field.